2015
DOI: 10.1371/journal.pone.0134185
|View full text |Cite
|
Sign up to set email alerts
|

The Participation of HPV-Vaccinated Women in a National Cervical Screening Program: Population-Based Cohort Study

Abstract: BackgroundConcerns have been raised that HPV-vaccination might affect women’s cervical screening behavior. We therefore investigated the association between opportunistic HPV-vaccination and attendance after invitation to cervical screening.MethodsA cohort of all women resident in Sweden, born 1977-1987 (N=629,703), and invited to cervical screening, was followed October 2006 - December 2012. Invitations to screening were identified via the National Quality Register for Cervical Cancer Prevention, as was the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 23 publications
8
42
0
1
Order By: Relevance
“…Of course, lack of vaccination in this setting could be associated with social deprivation because the catch-up campaign did carry a greater risk of not accessing disadvantaged children than was the case with the schools-based programme for 12-to 13-year-olds. A similar finding 68 of greater uptake of cervical screening among vaccinated women was recently reported from Sweden among women aged 25-35 years. A recently published Scottish study 69 found that the rate of uptake among unvaccinated women was only 65% of that DISCUSSION NIHR Journals Library www.journalslibrary.nihr.ac.uk among vaccinated women.…”
Section: Effect Of Prior Human Papillomavirus Vaccinationsupporting
confidence: 86%
“…Of course, lack of vaccination in this setting could be associated with social deprivation because the catch-up campaign did carry a greater risk of not accessing disadvantaged children than was the case with the schools-based programme for 12-to 13-year-olds. A similar finding 68 of greater uptake of cervical screening among vaccinated women was recently reported from Sweden among women aged 25-35 years. A recently published Scottish study 69 found that the rate of uptake among unvaccinated women was only 65% of that DISCUSSION NIHR Journals Library www.journalslibrary.nihr.ac.uk among vaccinated women.…”
Section: Effect Of Prior Human Papillomavirus Vaccinationsupporting
confidence: 86%
“…We therefore made adjustments for parental education as a marker for socioeconomic status. We have also found in a previous study that women vaccinated in the opportunistic HPV‐vaccination program were equally, if not more likely, to attend the cervical screening program in Sweden at age 23 and onwards . Thus, higher cervical screening attendance among vaccinated women could result in a detection bias of relatively more cervical lesions in vaccinated compared to unvaccinated women and could result in underestimation of the impact of vaccination on high‐grade cervical lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, opportunistic HPV-vaccination was associated with an equal or higher attendance after invitation to cervical screening [47]. …”
Section: Screening Conditional On Vaccination Statusmentioning
confidence: 99%